Efek Pestisida Sevin 85 SP Terhadap Hama Kumbang Tanduk ( Oryctes rhinoceros ) Di Pembibitan Main Nursery Kelapa Sawit ( Elaeis guineensis Jacq) - Dungo Silaban; Novilda Elizabeth Mustamu; Siti Hartati Yusida Saragih (JURNAL MAHASISWA AGROTEKNOLOGI (JMATEK), 2020)
Oil Paim seeding one of the first oil Paim treatments in pre nursery and main nursery Sevin 85 SP pesticides reduce pest infestation on planst, sevin pesticides which can control various pest attack beetles orytes rhinoceros horn beetles Orytes rhinoceros horn beetles in paim nurseries peramater observations include the length of the hole hole, the number of pests on plants , sevin pesticides which can control various attacks of beetle horn horns Orytes rhinoceros in nurseries oil paim peramater the test leaves consisted of 3 treatments of control S1 2 gr / 100 ml S2 3 gr / 200 ml from the resuts of the S3 study with fewr ham attacks.Key words : Pesticida Sevin 85 SP, Hornn beet, effects of pesticides, oil paim seeds